(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the contemporary adaptation of Phulkari embroidery in the realm of fashion and textile industry. Phulkari, a traditional embroidery art form from Punjab, India, holds deep cultural significance and is recognized as an integral part of Punjabi heritage. However, with changing times and evolving fashion trends, Phulkari has undergone a transformation to cater to the demands of modern consumers while retaining its cultural essence. This paper examines the ways in which Phulkari has been adapted and integrated into fashion and textile designs, exploring its relevance, impact, and potential challenges faced in this process.